Food tourism in the touristic development pole of the western region – Portugal - Oliveira, Simão (2017)
Currently, tourism is characterized by significant changes in its supply. These changes are motivated by the need of adjustment to the actual demand, which seek new types of experiences, different sensations and new destinations. Regarding tourist behavior, we can identify that there are profound changes, today, in comparison to previous years. Tourists travel more annually (but with shorter stays), are more knowledgeable about the destinations and products offered (playing, in this case, the internet a very important role) seeking new sensory experiences that are compelling, often to release accumulated labor stress resulting from a competitive urban society. As a result of these changes, niche tourism (also called thematic tourism), has gained an increasing interest from the tourism industry (supply) as well as by the academic community, which particularly in the mid-90s, began to turn more of its attention to this new way of supplying and practicing tourism. Food tourism in academic terms only began to receive greater attention in the beginning of this century. However, it has been relegated, to a secondary plan, in comparison with other types of niche tourism, such as wine tourism, ecotourism or even sports tourism. Therefore, it is easy to understand that all the studies about food tourism are relevant to increment the state of the art. This article results from a research project in the Western Region of Portugal, which had the duration of one year (May 2010 to May 2011) with a team of five investigators and two fulltime research fellows. This region is gastronomically rich, especially on fish, which attracts visitors to the area. Thus, among others, the following objectives were outlined for the study: Assess the potential of food tourism in the Western Touristic Pole; assess the local tourist agents’ perception on food tourism and their sensibility of the same; to profile the food tourist that travels to the Western Touristic Pole; and identify key practices of those who travel, motivated by food. In terms of methodology, the case study approach was used, with field work that resulted in 863 questionnaire surveys on the demand side and 92 questionnaire surveys on the supply side, resulting in a very interesting sample. The conclusions of the project revealed that food can actually be an important factor as a primary attraction, as well as secondary; that although the local agents are aware, the non-structure of a concrete product, results in a predominance of day visitors; there is little promotion of this tourism product; and it was possible to identify the profile of food tourists that visit the region.